The Third-Party Funding in Arbitration: A Challenge in Times of Crisis (European Journal of Marketing and Economics, 2021)
Arbitration as a way of resolving disputes between companies is essentially linked to the advantages of arbitration, especially with the speed and neutrality of arbitration, as well as the confidentiality, the possibility of choosing arbitrators with precise technical knowledge in the area of litigation, among others. The parties choose arbitration as a means of resolving disputes, relating to interests of an equity nature, bearing in mind that for some legislators the emphasis is on the availability of rights, arising from the contractual relationship that unites them. The payment of costs is a sine qua non condition for the constitution of the arbitral tribunal. The parties must proceed with the payment of taxes and fees, respectively to the arbitration center they have chosen and the arbitrators they have chosen. Considering that the economic situation of the companies may fluctuate, either during the execution of the main contract, or when the dispute arises, the constitution of the arbitral tribunal and during the procedural iter, the possibility of financing the arbitration was outlined. Third-Party Funding is a figure that involves a third-party, unrelated to the litigation, who will defray the expenses due by one of the parties to the arbitration. It will have as a counterpart the participation in the eventual financial result achieved through the success of the arbitration. As a methodology, in addition to analyzing the state of the art, we will indicate real cases and the reasons for the growth of this instrument, without forgetting the ethical issues involved.
Keywords: arbitration, companies, disputes, ethic, financing.